The pH Effect on Dye Waste Elimination Using Photocatalytic and Electrocoagulation Combination Methods - Kustiningsih, Indar; Adiwibowo, Muhammad Triyogo; Astuti, Diah; Oktavia, Endah; Sari, Denni Kartika; Slamet, Slamet (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2022)
The textile industry is growing very rapidly, the dye waste produced if thrown away can damage the environment. The dye waste can be degraded by electrocoagulation process or using photocatalyst. Electrocoagulation is a process of destabilizing a suspension so that it forms or flocs that are easily separated with the help of an electric current. Titania nanotube arrays are a commonly used photocatalyst. This catalyst is activated when exposed to light. The present study has investigated the impact of pH on the integration of electrocoagulation and photocatalysis processes. From the research conducted, it was found that the best waste degradation electrocoagulation process was at pH 10 with a decrease in dye reduction of 67.72%, for the photocatalyst degradation process the best results were at pH 10 with a decrease in dye reduction of 30.76%. The optimal conditions for the combination of photocatalysis and electrocoagulation were obtained at pH 10 with a reduction in dye waste of 71.6%.